Le coliving bruxellois. Un marché financiarisé où se côtoient bailleurs particuliers, investisseurs institutionnels et entreprises de gestion - Charlotte Casier (Belgeo)
This contribution examines the profiles of the players involved in the financialization of the private rental residential sector, in terms of ownership and management. It takes as a case study Brussels coliving, a real estate niche of high-standard furnished shared accommodation targetting young expatriates. This sector is run by coliving companies, which either manage properties owned by private landlords, or acquire buildings by raising capital from wealthy individuals, funds or listed companies. These two funding models give rise to different investment geographies. The contribution illustrates the variety of players involved in the financialization of real estate, confirming the plural nature of this process. It also highlights the key role of property managers as intermediaries between tenants and investors. Finally, it highlights the main contribution of local players in the financialization of an area.